2021
DOI: 10.7759/cureus.14488
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Appendiceal Diverticulum: An Incidental Finding During an Appendectomy

Abstract: Diverticula are small outpouchings that form at weak points in the wall of the digestive tract. They are commonly found in the colon, and while they can occur anywhere in the digestive tract, occurrence in the appendix is rare. Here, we report the case of a young woman presenting with complaints of right lower quadrant abdominal pain. The patient's physical examination, laboratory values, and computed tomography (CT) result supported the presumptive diagnosis of uncomplicated appendicitis. The patient underwen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Recently published articles highlighted the importance of preoperatively establishing the diagnosis due to its strong association with developing multiple complications [14]. Appendiceal perforation is one of its serious complications, specifically for the acquired type due to its thin wall and lack of muscular layer; moreover, the risk of perforation was found to be increased by fourfold compared to AA with a rate of 30-70% [6,15]. In addition to perforation, it has a risk for pseudomyxoma peritonei, gastrointestinal hemorrhage, pelvic pseudocyst formation, and the formation of appendicovesical fistula [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently published articles highlighted the importance of preoperatively establishing the diagnosis due to its strong association with developing multiple complications [14]. Appendiceal perforation is one of its serious complications, specifically for the acquired type due to its thin wall and lack of muscular layer; moreover, the risk of perforation was found to be increased by fourfold compared to AA with a rate of 30-70% [6,15]. In addition to perforation, it has a risk for pseudomyxoma peritonei, gastrointestinal hemorrhage, pelvic pseudocyst formation, and the formation of appendicovesical fistula [15].…”
Section: Discussionmentioning
confidence: 99%
“…Appendiceal perforation is one of its serious complications, specifically for the acquired type due to its thin wall and lack of muscular layer; moreover, the risk of perforation was found to be increased by fourfold compared to AA with a rate of 30-70% [6,15]. In addition to perforation, it has a risk for pseudomyxoma peritonei, gastrointestinal hemorrhage, pelvic pseudocyst formation, and the formation of appendicovesical fistula [15]. Furthermore, a recently published study suggested a prophylactic appendectomy if the AD was found incidentally on radiological investigations due to its strong association with malignancy, mainly carcinoid tumors and mucinous adenomas [14,16].…”
Section: Discussionmentioning
confidence: 99%
“…Congenital diverticula are true diverticula resulting from an abnormal bowel recanalization during the solid phase [7,8], and are associated with "D" trisomy or cystic fibrosis [9,10]. Congenital diverticula are very rare, and are characterized by an invagination of the entire intestinal wall including the mucosa, submucosa and muscularis propria into a normal intestinal wall [11]. In contrast, acquired diverticula are caused by invagination of the mucosal and submucosal layers through weakened portion of the intestinal wall, and they occur due to an increased intraluminal pressure [3].…”
Section: Discussionmentioning
confidence: 99%